KEANEKARAGAMAN JENIS BURUNG DIURNAL DI PULAU TEMAJO KECAMATAN SUNGAI KUNYIT KABUPATEN MEMPAWAH KALIMANTAN BARAT - Kurniawan, Agis Juliram; Prayogo, Hari; Erianto, . (JURNAL HUTAN LESTARI, 2018)
Birds or Aves are members of vertebrates (vertebrates) who have feathers and wings. Bird wildlife is one of the natural resources that have an important role in human life in terms of economy, recreation, and tourism as well as in terms of education and science. The research was conducted from 29 Agustus – 23 September 2017 to record the diversity of diurnal bird species in Temajo Island Sungai Kunyit Subdistrict Mempawah Regency. The research is expected to provide data and information on the diversity of diurnal bird species, so it can be the consideration in the effort of wildlife conservation of birds in the future especially in Temajo Island, Sungai Kunyit Subdistrict Mempawah Regency. The result of observation on eight paths was found as many as 98 species of birds were conducted in Temajo Island, Sungai Kunyit Subdistrict. On the first track was recorded 47 species of birds with a total of 244 individuals belonging to 24 families and while on the eighth track was recorded 48 species of birds with a total of 271 individuals belonging to 22 families.Keyword : Bird Diurnal, Diversity, Temajo Island.